2023
DOI: 10.1099/mic.0.001418
|View full text |Cite
|
Sign up to set email alerts
|

Clostridioides difficile spores tolerate disinfection with sodium hypochlorite disinfectant and remain viable within surgical scrubs and gown fabrics

Humaira Ahmed,
Lovleen Tina Joshi

Abstract: Clostridioides difficile is the most common cause of antibiotic-associated diarrhoea globally. Its spores have been implicated in the prevalence of C. difficile infection due to their resistance and transmission ability between surfaces. Currently, disinfectants such as chlorine-releasing agents (CRAs) and hydrogen peroxide are used to decontaminate and reduce the incidence of infect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
13
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(24 citation statements)
references
References 51 publications
(135 reference statements)
1
13
1
Order By: Relevance
“…Our findings provide reassurance that EPA-registered sodium hypochlorite disinfectants remain effective against C. difficile spores, including an isolate recently reported to exhibit tolerance to sodium hypochlorite (R20291) [3]. In previous studies, EPA-registered chlorine-releasing products have been shown to be effective in reducing spores on surfaces in clinical settings [15, 16].…”
Section: Full-textsupporting
confidence: 69%
See 2 more Smart Citations
“…Our findings provide reassurance that EPA-registered sodium hypochlorite disinfectants remain effective against C. difficile spores, including an isolate recently reported to exhibit tolerance to sodium hypochlorite (R20291) [3]. In previous studies, EPA-registered chlorine-releasing products have been shown to be effective in reducing spores on surfaces in clinical settings [15, 16].…”
Section: Full-textsupporting
confidence: 69%
“…commercial product registered with the EPA as a sporicide versus a preparation not registered as a disinfectant) or test methods. For example, shows variable results for spores of the R20291 isolate in several studies evaluating chlorine-releasing agents [3–5, 9–12], with several studies demonstrating that chlorine-releasing disinfectants remain effective [9–11]. Given these considerations, more information on the sodium hypochlorite formulation (i.e.…”
Section: Full-textmentioning
confidence: 99%
See 1 more Smart Citation
“…We read with interest the article by H. Ahmed and L.T. Joshi about the tolerance of Clostridioides difficile (CD) spores to disinfection with sodium hypochlorite disinfectant [ 1 ]. As reported in this study, the susceptibility of CD spores to chemical disinfectant is of paramount importance because the hospital environment is highly contaminated with C. difficile spores and can be a source of infection, especially in an outbreak setting [ 1 ].…”
mentioning
confidence: 99%
“…Joshi about the tolerance of Clostridioides difficile (CD) spores to disinfection with sodium hypochlorite disinfectant [ 1 ]. As reported in this study, the susceptibility of CD spores to chemical disinfectant is of paramount importance because the hospital environment is highly contaminated with C. difficile spores and can be a source of infection, especially in an outbreak setting [ 1 ]. The 2014 IDSA/APIC and 2018 ESCMID guidelines advocate for the use of hypochlorite or chlorine releasing agent for room disinfection of C. difficile infection (CDI) patients [ 2 3 ].…”
mentioning
confidence: 99%